KEBIJAKAN FORMULASI UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK PASAL 27 AYAT (3) DALAM PEMBAHARUAN HUKUM PIDANA - Suharto, Hary; Ramadhani, Rizki (Bahasa Indonesia, 2022)
This study aims to find out whether the background of the framers of the law at the formulation stage formulates the contents of Article 27 paragraph (3) of the ITE Law. How is the formulation of policies at the formulation stage of Article 27 paragraph (3) of the ITE Law in the renewal of criminal law. The method used is inormative legal research, the approach used is the statutory approach and the historical approach, legal materials are obtained from secondary data by means of library studies. Regarding the background of the framers of the law, formulating Article 27 paragraph (3) of the ITE Law is easy to be published in media that uses electronic means, its spread is very fast and widespread in the cyber world, destructive power of loading insult and / or defamation material, has effective destructive power against a person or group of people, electronic (cyber) media will be able to be used as the most effective option. The policy formulation of Article 27 paragraph (3) of the ITE Law in the renewal of criminal law, is given an explanation in the statement of the intention of contempt and / or defamation, clear limits are determined against the element of contempt and / or defamation Article 27 paragraph (3), the existence of justification reasons as contained in Article 310 paragraph (3) of the Criminal Code.